A Weak Formulation for Solving the Elliptic Interface Problems with Imperfect Contact. Issue 5 (11th July 2017) - Wang, Liqun; Hou, Songming; Shi, Liwei
Abstract: We propose a non-traditional finite element method with non-body-fitting grids to solve the matrix coefficient elliptic equations with imperfect contact in two dimensions, which has not been well-studied in the literature. Numerical experiments demonstrated the effectiveness of our method.